Implementation of the School Literacy Movement in Fostering Reading Interest in Elementary School Students - Nanazah Atika Sari; Dewi Widiana Rahayu; Suharmono Kasiyun; Syamsul Ghufron (Jurnal Sekolah Dasar, 2022)
The School Literacy Movement is an activity initiated by Directorate General of Education of Indonesia which aims to increase students' interest in reading at school. Application the school literacy movement continues to be carried out with the hope that students have the ability to access, understand, use writing information, and have the ability to speak. This study aims to describe implementation of the school literacy movement in increasing interest read students in elementary school. The method used is literature review with data collection techniques using the PRISMA principle data base Google Scholar 2017-2021 which was later in-depth analysis. The results of the study that in increasing interest in reading elementary school students can be marked by love, interest, and enthusiasm in reading books can be seen from the results of the forms of works made such as poetry, rhymes, stories short, competitive achievements and good literacy skills students have. Supporting factors in the implementation of the literacy movement schools include the existence of financial resources, reading parks, corners class reading, school library, interesting reading material, clean and comfortable environment. While the inhibiting factor the school literacy movement, namely the lack of teacher awareness and motivation from the teacher, reading materials used in activities literacy does not attract the attention of students and infrastructure in unsupportive schools.